Peningkatan Kompetensi Penelitian Tindakakan Kelas Untuk Guru-Guru Yayasan Pendidikan Bersama Kecamatan Berastagi - Ginting, Hartono; Silaen, Jonni Hamonangan; Laoli, Yulifati; Ginting, Jasa (Politeknik Negeri Medan, 2024)
In their profession as teachers, teachers do not just teach in class or provide extracurricular activities outside the classroom. More than that, teachers are also expected to be able to produce written work or research to support their professionalism actively. The number of teachers at Masehi Berastagi Private High School has 64 teachers with bachelor's level education and a total of 568 students. Based on information, teachers' lack of interest in conducting classroom action research or scientific work is due to the reasonably heavy teaching workload, a lack of motivation to carry out research, and a lack of knowledge to process research data using computers, especially using MS Excel and SPSS software. To overcome the problems faced by the teachers mentioned above, we provide training on how to create scientific work and how to process research data using Microsoft Excel and SPSS software. With direct practical training materials and methods in the computer laboratory, teachers who take part in the training can gain knowledge and skills that will be used to process research data so that it can motivate teachers to carry out research to create scientific work, which in turn will improve the quality of education. and teacher welfare. Implementation of service activities on Saturday, September 7, 2024, with 24 teachers participating. The average pretest score was 71.46, with a standard deviation of 4.54, and the average post-test score was 84.17, with a standard deviation of 4.34. This shows that there was an increase in knowledge after implementing this training activity. Namely, the average increased by 12 .71 value; in terms of standard deviation, it has also decreased so that it can be said that the differences in participants' knowledge are more evenly distributed so that increasing knowledge can motivate for teachers to carry out research to create scientific work which in turn will improve the quality of education and teacher welfare.